SURG-07. SURGICALLY TREATED BRAIN METASTASES FROM UTERINE ORIGIN: A CASE SERIES AND SYSTEMATIC REVIEW. (14th November 2022) - Eatz, Tiffany; Levy, Adam; Bystrom, Laure; Morell, Alexis; Merenzon, Martin; Higgins, Dominique; Eichberg, Daniel; Kader, Michael; Guyot, Manuela; Schlumbrecht, Matthew; Patel, Nitesh; Shah, Ashish; et al.
Abstract: INTRODUCTION: Brain metastases from uterine origin have an incidence of 0.7-1.1%. Due to their rarity, there exists scarce literature entailing their neurosurgical treatment and outcomes. OBJECTIVE: To report case management and outcomes of nine patients with brain metastases from uterine origin, as well as a systematic literature review findings focused on their neurosurgical treatment and outcomes. METHODS: This study was divided into two parts: (1) a retrospective, single-center patient series assessing neurosurgical outcomes in patients with primary uterine cancer with brain metastases and (2) a systematic review of the literature between 1980 and 2021 assessing outcomes of patients with primary uterine cancer metastasized to the brain. RESULTS: We report a case series at our single institution consisting of nine patients identified to have metastases to the brain from uterine origin that were treated with neurosurgical intervention. A total of 26 CNS lesions were identified among the 9 cases, with a mean number of lesions of 2.9 (1-7). The median age at the time of primary uterine cancer diagnosis was 49 years (26-80 years), with a median time from diagnosis to CNS metastasis of 19.5 months (3-54 months). The most common cerebral regions affected were the frontal lobe (42.3%) and the cerebellum (23%). Median progression free survival (PFS) and overall survival (OS) following intervention were 6.5 and 17.4 months, respectively. Stereotactic radiosurgery (SRS) alone resulted in the highest PFS and OS of 20.3 and 39 months, respectively. Sixteen studies were included in the systematic analysis. The mean OS was 13.3 months (3-41.1 months). CONCLUSION: Brain metastases from uterine origin seem to most frequently result in multiple symptomatic lesions with additional concurrent metastasis to other organs. The most effective treatment modality appeared to be SRS alone. There is limited data on sole SRS treatment, so additional research regarding this modality is encouraged.